The Concept of Children's Faith Education (Comparative Study Abdullah Nashih Ulwan and Zakiah Daradjat Thoughts) - Rezka, Aulia Gita; Subandi, Subandi; Amiruddin, Amiruddin (CV. Creative Tugu Pena, 2024)
The article aims to describe the children's faith education on comparison of Abdullah Nashih Ulwan and Zakiah Daradjat Thoughts. The research methodology applied in this study is literature review, also known as library research. Primary data sources consist of works by Abdullah Nashih Ulwan, such as